PENGGUNAAN FOTO UDARA DALAM PENILAIAN KERUSAKAN TAJUK AKIBAT EKSPLOITASI HUTAN - Ishak Sumantri; Wesman Endom (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
An investigation of the impact of logging operations on crown damage by using the aerial photograph of forest areas of PT. INHUTANI II in Pulau Laut, South Kalimantan was carried out.The results of the investigation lead to the following conclusions:1. Panchromatic black and white aerial photograph of 1:20.000 scale is good enough to use for evaluating the damage of dominant and codominant crowns and crown closure of the trees. It is found that the crown of 11 trees/ha were damaged, consisted of 9 tree crowns were damaged partially and 2 tree crowns were damaged totally.2. Steeper terrains caused larger decrease of crown closure of the trees. On the slope of 0-15%, 25-45% and 45% and above, the crown closure reductions were 61%, 76% and 80%, respectively